Resolvemos ecuaciones simples con números naturales - Díaz Díaz, Gomer (2019)
The present sufficiency work has been prepared for boys and girls of the fifth grade of primary education, of the city of Trujillo in the year 2019, with the theme “We solve simple equations with natural numbers”, in which everyday situations have been taken into account in which students establish relationships between data and unknown values of an equivalence and variation relations between data of two magnitudes, and transform them into simple equations with natural numbers._x000D_ In the elaboration of the session we have worked with the pedagogical and didactic processes of the area of mathematics to promote significant learning._x000D_ The strategies used were designed to promote the active and meaningful participation of all students._x000D_ It is intended at all times to awaken the interest and motivation of the student in mathematics, since it is a very important and valuable area.